Effects of Problem - Solving Approach to Teaching Mathematics on Students’ Achievement in Secondary School in Murang’a County, Kenya - Kigamba, John Gakinya (Machakos University Press, 2019)
This study examined the effects of problem – solving to teaching of Mathematics on students’ achievements in secondary schools in Murang’a County. The study was guided by the following four objectives to: establish the preference for conventional strategies in teaching Mathematics over problem – solving strategies in teaching secondary school, compare students’ performance in Mathematics for those taught using problem - solving strategies with those taught using conventional strategies, assess the students change in attitude towards Mathematics when taught through problem - solving strategies and develop a prototype lesson plan for problem – solving in teaching of Mathematics in secondary schools in Murang’a County.
Keywords: Mathematics; Education Students; Examinations; Teachers